Polyphenols profile and antioxidant capacity of selected medicinal plants of Bangladesh - Shaheen, Nazma; Tukun, Avonti Basak; Islam, Saiful; Akhter, Kazi Turjaun; Hossen, Md Sujan; Longvah, Thingnganing (Bioresearch Communications, 2021)
Polyphenols in many plant foods have received a great deal of attention due to their biological potency and postulated protective role against certain non-communicable diseases like cancer, neurodegenerative disease, and cardiovascular disease. The current study focuses on 15 indigenous plants which are traditionally being used for medicinal and other purposes in Bangladesh. Specifically, this study aimed to determine the total phenolic content (TPC), profile the polyphenolic composition, and assess the antioxidant capacity (AC) of water and methanol extracts derived from these plants. The TPC was estimated using the Folin-Ciocalteu method, and DPPH inhibition was used to assess the AC. HPLC-centered simultaneous determination method of polyphenols was employed to identify and quantify individual polyphenolic compounds. TPC content (expressed as mg GAE/100 g FW) ranged from 15.5 (Zanthoxylum rhetsa) to 276.9 (Moringa oleifera). The lowest IC50 in the water and methanol extracts were shown by Moringa oleifera and Zanthoxylum rhetsa respectively and they also exhibited high free radical scavenging activity in the corresponding solvents (91.9% and 92.9% DPPH inhibition by Moringa oleifera and Zanthoxylum rhetsa respectively). The lowest DPPH inhibition was observed in Alternanthera philoxeroides (29.8%) and Spilanthes calva (24.5%) in the water and methanol extracts respectively. Ten polyphenols (coumaric acid, chlorogenic acid, caffeic acid, apigenin, apigenin-7-O-neohesperidoside, quercetin-3-β-D-glucoside, luteolin, quercetin-3-O-β-D-glucopyranoside, isorhamnetin and kaempferol) were initially identified and subsequently quantified in the plant extracts. Spilanthes calva, Moringa oleifera, Oxalis corniculata, and Piper retrofractum contained the highest amount of coumaric acid and chlorogenic acid, apigenin, caffeic acid and apigenin-7-O-neohesperidoside respectively. Senna tora had the greatest amount of kaempferol, quercetin-3-β-D-glucoside, and isorhamnetin whereas luteolin and quercetin-3-O-β-D-glucopyranoside were observed to be the maximum in Alternanthera sessilis. To conclude, Moringa oleifera and Senna tora with high percentage of DPPH inhibition and low IC50 were the most potent antioxidant sources among the analyzed samples. Bioresearch Commu. 7(1): 947-954, 2021 (January)